Pengembangan lembar kerja siswa materi fisika bermuatan literasi baru untuk meningkatkan hasil belajar fisika siswa kelas XI SMA - Annisa N; Asrizal A; Fatni Mufit (Universitas Negeri Padang, 2020)
Human resources are required to have broad insights, think critically, and have literacy to deal with the development of 21st century education. The 2013 curriculum is designed to challenge 21st century education and is taught so that the mindset with mastery of student literacy increases. Literacy activities must be integrated in learning physics in the 2013 curriculum. However, the challenge in schools is that integration of student literacy was not good. One solution to solve this problem is to develop a new Literacy Physics worksheet. The purpose of this research was to determine the validity and practicality of the use of Physics Worksheet with new literacy. This research is a type of Research and Development (R&D). The object of this research was the Physics Worksheet with new literacy. Data sources from this study were the results of preliminary studies, the results of the validation assessment, and the results of the practicality assessment. Data collection instruments in this result were observation sheets, validity test sheets, and practicality test sheets. The data analysis technique used is document analysis for preliminary studies and descriptive statistical analysis for product validation and clarity. Based on data analysis three research results can be presented. First, the preliminary study consisted of observations regarding the application of new literacy that were done in a low grade with an average value of 38.045, the results of the initial knowledge test of students at SMAN 5 Padang were low with an average value of 39.29 and the results of the work analysis in three mathematics textbooks Class XI high school students are classified as low with an average value of 32.78. Second, validity of Physics worksheet is very good with average value 81.15. Third, practicality of Physics worksheets literacy of new according to teachers and students respectively is very good with average value of 85.5 and 86.79 respectively. Physics worksheet filled with new literacy for class XI high school students is valid and practical